The Children's Responsibility toward Parents Deposited in Social Foundations in Review of Law No. 1 of 1974 - Anggraini, Melinna; Syahmedi Siregar, Ramadhan (Universitas Islam Sultan Agung, 2023)
This research aims to know that the obligation of a child is to be devoted to his parents including being responsible for the alimony of the care of both parents as mandated by Law No. 1 of 1974. This research uses empirical juridical research method with statutory approach and case approach. The results of this study prove that the care of parents by children in nursing homes due to the wishes of the parents themselves is makruh. The makruh law can change to haram, if the child after leaving his parents in the foundation, does not show good manners, such as relinquishing responsibility as a child. The law is permissible if the child does the entrustment for the good of the parents and the child still carries out the obligations and fulfills the rights of his parents who live in the nursing home. In the view of Law No. 1 of 1974 itself, children are obliged to take care of all the needs of their parents even though they are in a nursing home because this is an obligation of alimony of children to their parents.